Mitochondrial fusion heterogeneity drives bidirectional tumor phenotypic transition in combined hepatocellular–cholangiocarcinoma - Lin Chen; Dalin Wang; Weidong Qin; Gang Wang; Dan Wu; Jiaying Li; Xingchen Wang; Yinping Wang; Xiacheng Sun; Jing Zhao; Shanshan Guo; Lele Ji; et al. (Proceedings of the National Academy of Sciences, 2026)
Dysregulation of mitochondrial dynamics modulates malignant cell fate; however, the substantial heterogeneity in mitochondrial dynamics among tumor cells within individual tumor nodules and the resultant functional consequences remain inadequately characterized. In this study, we induced mosaic impairment of mitochondrial fusion in mouse liver under tumorigenic conditions and unexpectedly identified the formation of combined hepatocellular-cholangiocarcinoma (cHC), a monoclonal tumor displaying features of both hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC). Restoration of the mitochondrial fusion protein MFN1 effectively suppressed cHC development. Analysis of human cHC samples revealed that ICC-like cells exhibit more pronounced mitochondrial fusion impairment compared to HCC-like cells. Mechanistically, increasing impairment of mitochondrial fusion resulted in a dose-dependent elevation of reactive oxygen species (ROS). Low levels of ROS upregulated HNF4α, promoting HCC-like differentiation, whereas high ROS levels activated HES1, facilitating ICC-like differentiation. Collectively, these results demonstrate that heterogeneity in mitochondrial dynamics is a critical determinant of cHC path-ogenesis.